Bonds in Islamic Economic Review - Abu Umar Faruq (Fakultas Ekonomi dan Bisnis Islam, 2022)
Bonds that are reviewed from fiqh principles are allowed as stated in the DSN MUI fatwa Number: 32/DSN-MUI/IX/2002 concerning Syari'ah Bonds, Number: 41/DSN-MUI/III/2004 concerning Syari'ah Ijarah Bonds and Number: 59 /DSN-MUI/V/2007 concerning Convertible Syari'ah Mudharabah Bonds. Bonds can be issued based on sharia principles by referring to the fatwa. This study aims to describe bonds in a review of fiqh rules and describe the differences between Islamic bonds and bonds. with qualitative research methods. This study found that the basic difference between Islamic bonds and conventional bonds is the application of interest that has been determined at the beginning of the transaction. In Islamic bonds, profit sharing is not determined at the beginning of the transaction, but what is determined is the percentage (nisbah) of future profits.